Chaos and Its Control in a Fractional Order Glucose-insulin Regulatory System - Dousseh, P. Y.; Hinvi, L. A.; Miwadinou, C.H.; Monwanou, A. V.; Orou, J. B. Chabi (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, dynamic behaviors and chaos control of a Fractional Order Glucose-Insulin Regulatory System (FOGIRS) recently introduced in the literature are studied. Some interesting behaviors such as periodic motions, antimonotonicity, and period-doubling route to chaos are observed. Besides, it is found that the minimum effective dimension for the system to generate chaos is 2.904 in the conmensurate order case and 2.882 in the incommensurate order case. To control chaos in this system, two controllers are designed. First, a feedback controller to stabilize the chaotic system to one of its equilibrium points, and a robust adaptive fractional order sliding mode controller is used to globally stabilize the chaotic FOGIRS with uncertain dynamics. Numerical simulations are used to show the effectiveness of those controllers.